Pelaksanaan Pra dan Pasca Musyawarah Perencanaan Pembangunan Desa Kertomulyo Kecamatan Margoyoso Kabupaten Pati - Dyah Erina Widia; Muhammad Adnan; Dzunuwanus Ghulam Manar (Journal of Politic and Government Studies, 2016)
This study was undertaken to explain how the stages of pre and post development planning in the Kertomulyo Village, Margoyoso District of Pati regency. From the data processing research shows that the stages of pre Musrenbang village is an activity with a long process and just not a technical preparations such as the spread of invitations, the place settings and consumption. The main activities of the pre musrenbang village is a substance or material to prepare village plans better. Activities that must be performed after Musrenbang are: Publishing News Musrenbang events, work meetings finalization of the document RKP Village, determination decree village head, village delegation debriefing team, and delivery of RKP village of the Village Head to Sub-district Head. Public participation in the implementation of Musrenbang getting better, it can be proved with attendance increasing every year. However, women's participation is still lacking in rural development planning.Keywords: Rural Development Planning Meeting, the public participation.